HUBUNGAN ANTARA GAYA KOMUNIKASI KEPALA SEKOLAH DENGAN KINERJA PENDIDIK DI SMK NEGERI 3 JAYAPURA - MARIA CHRISANTI HOAR; MEYLANI A TIJOW; DIKI KURNIAWAN (Universitas Cenderawasih, 2020)
This research aims to determine the principal's communication style and the teachers’ performance at SMK Negeri 3 Jayapura, and also to find out the significance relation between both. This was a quantitative research. The population that is used was 110 that is include the principal and the teachers. Sample that is used was 86 people with significant level of 0.05%. Data collection was carried out using questionnaires and documentation. Data analysis was performed using product moment correlation and using SPSS version 23 for windows. Based on the results, this research showed that: (1) The principal’s communication style in SMK Negeri 3 Jayapura is in the high category with a mean of 109.49 and a standard deviation of 11.118. (2) The teachers’ performance in SMK Negeri 3 Jayapura is in the high category with a mean of 157.26 and a standard deviation of 18.671. (3) There is no significant relation between the principal’s communication style and the teachers’ performance at SMK Negeri 3 Jayapura. It showed by rhitung 0,066≤ rtabel 0,220.Keywords: Communication Style, Teachers, Teacher's performance, com munication and performance of Teachers.